Pengaruh pengolahan terhadap Pati Resisten Pisang Kepok (Musa paradisiaca fa. typica) dan Pisang Tanduk (Musa paradisiaca fa. corniculata) - Yustinus Marsono (agriTECH, 2002)
A study on the effect processing on resistant starch (RS) content and chemical composition of kepok (Musa paradisiaca fa. typica) and tanduk banana (Musa paradisiaca fa. corniculata) has been conducted. Mature banana was steamed, steamed - cooled, steamed - frozen, dried and dried - fried and was analyzed for starch, RS, simple sugars and chemical composition. RS content was determined by enzymatic method. It was found that steaming chaned RS from 6.2 mg/g to 9.5 mg/g (53%) for kepok banana and from 7.5 mg/g to 10.5 mg/g (40%) for tanduk banana. Cooling the steamed banana increased the RS to 6.8 mg/g (kepok) and 9.7 mg/g (tanduk). Freezing of the steamed banana increased the RS content by 30% (8.1 mg/g) and 24% (9.3 mg/g) for kepok and tanduk banana, respectively. RS of kepok and tanduk banana increased after the bananas were dried (15% and 41%) and dried-fried (53% and 55%). Small changes were shown on the chemical composition of the banana after processing, except that frying increased the fat content significantly.